Bakti Sosial Untuk Meningkatkan Motivasi Pasien Penderita Kanker di Rumah Pejuang Kanker Ambu - Fadli Agus Triansyah; Sandi Jembar Wijaya; Rini Melani; Erna Dwi Jayanti; Nurhuda Teapon (Universitas 45 Surabaya, 2023)
Cancer is defined as a disease that originates from the progressive and abnormal growth of body cells. This condition is caused by changes in deoxyribonucleid acid (DNA), so that cells lose their normal function. This service aims to provide motivation to cancer sufferers at the Ambu Cancer Fighting House to increase their zest for life and provide happiness to cancer sufferers. Some of the activities carried out were painting classes, cooking classes, wishing trees and provision of basic necessities. Based on some of the activities carried out, it is hoped that some changes will occur, namely increasing the motivation of younger cancer fighters, increasing the ability of younger cancer fighters in painting, increasing the ability of younger cancer fighters in cooking, increasing the confidence of younger cancer fighters that hope is always there and lightens the burden on managers by providing basic food donations.